Microbial Communities in a High Arctic Polar Desert Landscape - McCann, Clare M.; Wade, Matthew J.; Gray, Neil D.; Roberts, Jennifer A.; Hubert, Casey R. J.; Graham, David W. (Frontiers in Microbiology, 2016)
The High Arctic is dominated by polar desert habitats whose microbial communities are poorly understood. In this study, we used next generation sequencing to describe the α- and β-diversity of polar desert soils from the Kongsfjorden region of Svalbard. Ten phyla consistently dominated the soils and accounted for 95 % of all sequences, with Proteobacteria, Actinobacteria and Chloroflexi being the dominant lineages. In contrast to previous investigations of Arctic soils, Acidobacterial relative abundances were low as were the Archaea throughout the Kongsfjorden polar desert landscape. Lower Acidobacterial abundances were attributed to the circumneutral soil pH in this region which has resulted from the weathering of the underlying carbonate geology. In addition, we correlated previously measured geochemical variables to determine potential controls on the communities. Soil phosphorus, pH, nitrogen and calcium significantly correlated with β-diversity indicating a landscape scale lithological control of soil nutrients which in turn influenced community composition. In addition, soil phosphorus and pH significantly correlated with α- diversity, specifically the Shannon diversity and Chao 1 richness indices.